Lauric Acid Is an Inhibitor of Clostridium difficile Growth in Vitro and Reduces Inflammation in a Mouse Infection Model - Yang, Hsiao-Ting; Chen, Jenn-Wei; Rathod, Jagat; Jiang, Yu-Zhen; Tsai, Pei-Jane; Hung, Yuan-Pin; Ko, Wen-Chien; Paredes-Sabja, Daniel; Huang, I-Hsiu (Frontiers in Microbiology, 2018)
Clostridium difficile is a Gram-positive, spore-forming anaerobic human gastrointestinal pathogen. C. difficile infection (CDI) is a major health concern worldwide, with symptoms ranging from diarrhea to pseudomembranous colitis, toxic megacolon, sepsis, and death. CDI onset and progression are mostly caused by intestinal dysbiosis and exposure to C. difficile spores. Current treatment strategies include antibiotics; however, antibiotic use is often associated with high recurrence rates and an increased risk of antibiotic resistance. Medium-chain fatty acids (MCFAs) have been revealed to inhibit the growth of multiple human bacterial pathogens. Components of coconut oil, which include lauric acid, have been revealed to inhibit C. difficile growth in vitro. In this study, we demonstrated that lauric acid exhibits potent antimicrobial activities against multiple toxigenic C. difficile isolates in vitro. The inhibitory effect of lauric acid is partly due to reactive oxygen species (ROS) generation and cell membrane damage. The administration of lauric acid considerably reduced biofilm formation and preformed biofilms in a dose-dependent manner. Importantly, in a mouse infection model, lauric acid pretreatment reduced CDI symptoms and proinflammatory cytokine production. Our combined results suggest that the naturally occurring MCFA lauric acid is a novel C. difficile inhibitor and is useful in the development of an alternative or adjunctive treatment for CDI.